Species traits - Yanjie, Xu; Si, Yali; Wang, Yingying; Zhang, Yong; Prins, Herbert; Cao, Lei; De Boer, Willem Frederik (Dryad Digital Repository, 2019)
Species names are abbreviated: ts - tundra swan (Cygnus columbianus); sg - swan goose (Anser cygnoid); bg - bean goose (Anser fabalis); gwfg - greater white-fronted goose (Anser albifrons); lwfg - lesser white-fronted goose (Anser erythropus); glg - greylag goose (Anser anser); ct - common teal (Anas crecca); np - northern pintail (Anas acuta).